IMPACT OF SPIN-OFF RESTRUCTURING TOWARDS EMPLOYEES’ BEHAVIOUR AND ATTITUDES - Mohd Senusi, Shahrullizam; Pangil, Faizuniah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Spin-off restructuring has become a prominent corporate strategy as multinational corporations pursue enhanced strategic focus, improved operational agility, and optimised shareholder value. However, despite the extensive financial literature examining market reactions and firm-level outcomes of spin-offs, comparatively limited attention has been devoted to their Human Resource (HR) implications, particularly employees’ behavioural, psychological, and attitudinal responses. This study addresses this gap by investigating how spin-off restructuring influences employee behaviour and attitudes within the context of the corporate separation of a large United States (US) based multinational industrial corporation that focuses on employees based in Malaysia. Adopting a qualitative phenomenological approach, this study draws upon semi-structured interviews with employees based in Malaysia who directly experienced the spin-off transition. The research explores employees’ interpretations of the restructuring rationale, their sensemaking processes during periods of uncertainty, and the evolution of motivation and organisational identity before and after separation. Notably, thematic analysis reveals that, while employees generally understood and accepted the strategic justification for the spin-off, the restructuring generated multidimensional uncertainty encompassing job security, career continuity, and identity stability. Leadership communication, perceived transparency, alignment with organisational purpose, and intrinsic motivation emerged as critical moderating variables in shaping employee adaptation. The study contributes to Human Resource Management (HRM) scholarship by conceptualising spin-off restructuring as a separation-based form of organisational change that challenges identity continuity and psychological contracts. Additionally, it underscores the importance of human-centred leadership, sustained communication strategies, and identity-sensitive HR interventions in preserving engagement during corporate separation.